VD_FINDINFO HC / 2012 / 362 vom 15. Mai 2012 - VD Tribunal cantonal (2012)
BAIL À LOYER, LOYER ABUSIF, LOYER INITIAL, FARDEAU DE LA PREUVE, PREUVE | 8 CC, 269 CO, 269a let. a CO, 270 CO, 11 al. 1 OBLF, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH), 317 al. 1 let. b CPC (CH)